2012
DOI: 10.1007/s00134-011-2450-7
|View full text |Cite
|
Sign up to set email alerts
|

Use of expiratory change in bladder pressure to assess expiratory muscle activity in patients with large respiratory excursions in central venous pressure

Abstract: Patients with large respiratory excursions in CVP often have significant expiratory muscle activity that will cause their CVP to overestimate transmural right atrial pressure. The magnitude of expiratory muscle activity can be assessed by measuring ΔIAP. Subtracting ΔIAP from the end-expiratory CVP usually provides a reasonable estimate of the CVP that would be obtained if exhalation were passive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…26 Expiratory muscle activity is not always clinically apparent, especially in obese patients. 27 Repeat assessment aft er a brief period of neuromuscular paralysis is recommended when auto-PEEP remains markedly elevated despite sedation. On occasion, unexpectedly low values of measured auto-PEEP can be seen in patients with fulminant asthma who are ventilated at very low respiratory rates, presumably due to airway closure that prevents accurate assessment of end-expiratory alveolar pressure.…”
Section: Assessment Of Hyperinfl Ationmentioning
confidence: 99%
“…26 Expiratory muscle activity is not always clinically apparent, especially in obese patients. 27 Repeat assessment aft er a brief period of neuromuscular paralysis is recommended when auto-PEEP remains markedly elevated despite sedation. On occasion, unexpectedly low values of measured auto-PEEP can be seen in patients with fulminant asthma who are ventilated at very low respiratory rates, presumably due to airway closure that prevents accurate assessment of end-expiratory alveolar pressure.…”
Section: Assessment Of Hyperinfl Ationmentioning
confidence: 99%
“…There is no standard for identifying active expiration on hemodynamic tracings. A simultaneous measure of Ppl with an esophageal pressure (Peso) measurement or even better combination with a gastric or bladder pressure 8,9 measurement would have been very helpful, but the use of these is limited and not practical in a large prevalence study. Some examples with Ppl measurement are discussed below.…”
Section: Discussionmentioning
confidence: 99%
“…Although active expiration is not infrequent and can cause major distortions in the hemodynamic tracings, 4,8,9 there is no established criteria for identifying it. We addressed this with a 2-step approach.…”
Section: Methodsmentioning
confidence: 99%
“…In a study on the influence of the expiratory muscle activity on end-expiratory CVP, Leatherman et al [60] showed that the changes in intra-abdominal pressure (ΔIAP) in 39 patients who had a respiratory excursion in CVP from end-expiration to end-inspiration (CVP(ee) − CVP(ei)) of at least 8 mmHg, the CVP variations overestimated the transmural right atrial pressure. However the authors showed also that the magnitude of expiratory muscle activity can be assessed by measuring ΔIAP.…”
Section: Hemodynamic and Cardiovascularmentioning
confidence: 99%